OS MUSEUS DE CULTURA POPULAR DE SÃO LUÍS COMO ESPAÇOS EDUCATIVOS: configurações e perspectivas para uma pedagogia do imaginário - Serra, Monique de Oliveira (2012)
Study the educational character in the museums of popular culture. Analyzes the museums of popular culture of St. Louis, Nhozinho s House and the Party s House, if they present themselves as educational spaces or tourism, taking into account the process of popular culture musealization Maranhão. Located in the complex paradigm, proposed by Morin (1990), which points to the valuation of humanistic studies and other knowledge. Reveals the museums as spaces for non-formal education, based on their own laws and guidelines that govern its operation, in the other words, that must act as places that educate. Notes that for the subjects involved in research - directors, guides and visitors - the local investigated are educational spaces for showing popular culture. Analyzes the collections of museums, in the light of Anthropological Theory of Imaginary developed by Durand (1997). Notes that the images of symbolization processes contribute as a factor in balancing the individual, the schemes, beside of contribute to a pedagogy the imaginary, rebalancing reason and emotion, science and poetry.